Different Angiogenic Abilities of Self-Setting Calcium Phosphate Cement Scaffolds Consisting of Different Proportions of Fibrin Glue. (9th June 2014) - Xiu, Jintao; Fan, Junjun; Li, Jie; Cui, Geng; Lei, Wei
Abstract : To investigate the different angiogenic abilities of the self-setting calcium phosphate cement (CPC) consisting of different proportions of fibrin glue (FG), the CPC powder and the FG solution were mixed at the powder/liquid (P/L) ratios of 1 : 0.5, 1 : 1, and 1 : 2 (g/mL), respectively, and pure CPC was used as a control. After being implanted into the lumbar dorsal fascia of the rabbit, the angiogenic process was evaluated by histological examination and CD31 immunohistochemistry to detect the new blood vessels. The result of the new blood vessel showed that the P/L ratio of 1 : 1 group indicated the largest quantity of new blood vessel at 4 weeks, 8 weeks, and 12 weeks after implantation, respectively. The histological evaluation also showed the best vascular morphology in the 1 : 1 group at 4 weeks, 8 weeks, and 12 weeks after the operation, respectively. Our study indicated that the CPC-FG composite scaffold at the P/L ratio of 1 : 1 (g/mL) stimulated angiopoiesis better than any other P/L ratios and has significant potential as the bioactive material for the treatment of bone defects.